Energy scaling of a narrowband, periodically poled LiNbO, nanosecond, nonresonant optical parametric oscillator - Temel,T; Murray,RT; Wang,L; Chen,W; Schirrmacher,A; Divliansky,IB; Mhibik,O; Glebov,LB; Petrov,V (Applied Optics, 2024)
We demonstrate that 3-mm-thick, periodically poled LiNbO enables energy scaling of a nonresonant optical parametric oscillator operated in the narrowband mode with a volume Bragg grating at the signal wavelength. Utilizing the full available pump power at 1064 nm, we obtained maximum average powers of 2.25 and 2.08 W for the signal (1.922 µm) and idler (2.383 µm) pulses at 10 kHz, at a total conversion efficiency of 32.8%, which represents a fourfold increase in terms of peak powers over our previous work. The signal and idler spectral linewidths were ∼ 1 nm, with pulse lengths of ∼ 6 ns and an idler beam propagation factor of ∼5.